1990
DOI: 10.1038/346760a0
|View full text |Cite
|
Sign up to set email alerts
|

Human cyclin A is adenovirus E1A-associated protein p60 and behaves differently from cyclin B

Abstract: CYCLINS are proteins synthesized during each cell cycle and abruptly destroyed in each mitosis. Cyclins have been implicated in the induction of mitosis and are associated with the serine-threonine protein kinase p34cdc2 as components of mitosis promoting factor (MPF). On the basis of conserved sequence motifs cyclins can be divided into A or B types. We recently cloned a human cyclin B and showed that cyclin B expression is regulated transcriptionally and post-translationally during the cell cycle, and that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
417
2
4

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 678 publications
(444 citation statements)
references
References 22 publications
21
417
2
4
Order By: Relevance
“…This nucleus showed no ongoing DNA replication as assayed by BrdU incorporation. To confirm the specificity of this immunofluorescence pattern further, we stained formaldehyde-fixed cells with two other polyclonal rabbit antisera raised against the entire human cyclin A protein (Pines and Hunter, 1990;Pagan0 et al, 1992b). These antisera react with a single protein from mouse cell extracts whose pattern of expression and association with cdc2-related kinases is consistent with it being the murine cyclin A (Hamaguchi et al, 1992; data not shown).…”
Section: Specific Localizationmentioning
confidence: 95%
See 3 more Smart Citations
“…This nucleus showed no ongoing DNA replication as assayed by BrdU incorporation. To confirm the specificity of this immunofluorescence pattern further, we stained formaldehyde-fixed cells with two other polyclonal rabbit antisera raised against the entire human cyclin A protein (Pines and Hunter, 1990;Pagan0 et al, 1992b). These antisera react with a single protein from mouse cell extracts whose pattern of expression and association with cdc2-related kinases is consistent with it being the murine cyclin A (Hamaguchi et al, 1992; data not shown).…”
Section: Specific Localizationmentioning
confidence: 95%
“…The homogeneous staining with SrdU is an effect of the continuous labeling. Note the nucleus that has not started replicating (SrdU-negative) and displays a dispersed distribution of cyclin A. Cyclin A was detected with rabbit polyclonal antiserum (Pines and Hunter, 1990) in (D) and with affinity-purified rabbit antibodies (Girard et al, 1991) in the remaining stainings; PCNA, with an anti-PCNA mouse monoclonalZO49 (Zymed); BrdU, with fluorescein-conjugated anti-BrdU monoclonal antibody (Boehringer Mannheim). C2SVTts myotubes were incubated for 1 day in T antigen-inducing conditions (GM plus Zn" at 33%).…”
Section: Specific Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, major bands representing these proteins were named after their apparent SDS-PAGE molecular mass (Harlow et al, 1986), that is, p60, p105, p107, p130 and p300. The subsequent characterization of these proteins first identified p105 as the product of the RB gene (Whyte et al, 1988), and then p60 as cyclin A (Giordano et al, 1989;Pines and Hunter, 1990). Later, genes encoding p107 (Ewen et al, 1991;Zhu et al, 1993) and pRb2/p130 (Hannon et al, 1993;Li et al, 1993;Mayol et al, 1993) were cloned using different strategies.…”
Section: And References Therein)mentioning
confidence: 99%